Morphological analysis of a local tissue response to subcutaneously implanted acellular dermal matrix fragments - K. I. Melkonyan; A. A. Verevkin; A. S. Sotnichenko; T. V. Rusinova; Ya. A. Kozmai; A. S. Asyakina; M. I. Kartashevskaya; K. G. Gurevich; I. M. Bykov (Бюллетень сибирской медицины)
Acellular dermal matrices (ADMs) are gaining popularity as surgical materials for operations on the pelvic organs, as well as in burn therapy and plastic surgery. Evaluation of the biocompatibility of surgical materials is an important and necessary step in the development of new ADMs.The aim of the study was to compare the results of subcutaneous implantation of ADM and native porcine skin in rats.Materials and methods. To obtain ADMs, detergent – enzymatic decellularization was used. On days 7, 14, 21, and 60 after the implantation of ADMs (the experimental group) and native porcine skin (the control group), the animals were removed from the experiment. The histologic sections were stained with hematoxylin – eosin and Masson’s trichrome stain, then an immunohistochemical reaction with antibodies to CD3 and CD68 was performed. Computer morphometry was carried out using the ImageJ software.Results. On day 7 after the implantation, moderate sterile inflammation in the experimental group and pronounced sterile inflammation with eosinophil infiltration in the control group were observed. On day 14 of the experiment, the samples from the experimental group were characterized by a relatively low content of macrophages and T-lymphocytes with insignificant edema and no signs of ADM biodegradation. The control group showed pronounced inflammation, a large number of infiltrating macrophages and T lymphocytes, as well as fragmentation of collagen fibers. On day 21 of the experiment, a thin capsule was formed around ADM, there was a small number of infiltrating T lymphocytes and macrophages, the collagen fibers of the implant were intact. In the samples of the control group, there was pronounced inflammation with the presence of a significant number of lymphocytes and macrophages, as well as fragmentation and vascularization of the implant. On day 60 of the experiment, no inflammatory response was observed around ADM, biodegradation was minimal, and a dense fibrous capsule was formed around the fragment of the native porcine skin.Conclusion. The experimental ADM has low immunogenicity and a low degree of biodegradation, which makes it possible to use it for further research to create efficient surgical material that is safe for use in clinical practice.